2021
DOI: 10.1007/s00253-021-11129-w
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of a Rieske non-heme iron oxygenase multicomponent system from Phenylobacterium immobile E DSM 1986 enables pyrazon cis-dihydroxylation in E. coli

Abstract: Phenylobacterium immobile strain E is a soil bacterium with a striking metabolism relying on xenobiotics, such as the herbicide pyrazon, as sole carbon source instead of more bioavailable molecules. Pyrazon is a heterocyclic aromatic compound of environmental concern and its biodegradation pathway has only been reported in P. immobile. The multicomponent pyrazon oxygenase (PPO), a Rieske non-heme iron oxygenase, incorporates molecular oxygen at the 2,3 position of the pyrazon phenyl moiety as first step of deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…By functional reconstitution of pyrazone oxygenase, it was possible to accomplish pyrazone dihydroxylation in E. coli JW5510. 95 Bernhard′s research focused next on the evaluation of the substrate scope of these enzymes. More than 300 substrates are described to be accepted by dioxygenases, which encompasses monocyclic aromatic compounds, polycyclic and heterocyclic arenes, substituted aromatics, halogenated arenes, and aromatic acids.…”
Section: Oxidation Of Olefins Aromatics and Aliphaticsmentioning
confidence: 99%
See 1 more Smart Citation
“…By functional reconstitution of pyrazone oxygenase, it was possible to accomplish pyrazone dihydroxylation in E. coli JW5510. 95 Bernhard′s research focused next on the evaluation of the substrate scope of these enzymes. More than 300 substrates are described to be accepted by dioxygenases, which encompasses monocyclic aromatic compounds, polycyclic and heterocyclic arenes, substituted aromatics, halogenated arenes, and aromatic acids.…”
Section: Oxidation Of Olefins Aromatics and Aliphaticsmentioning
confidence: 99%
“…In a very recent study, Hauer’s group reported the discovery of a multicomponent pyrazone oxygenase, a Rieske nonheme iron oxygenase, in Phenylobacterium immobile strain E. This strain contains not one but 19 different α-subunits encoded in its genome. By functional reconstitution of pyrazone oxygenase, it was possible to accomplish pyrazone dihydroxylation in E. coli JW5510 …”
Section: Vestige Of Bernhard′s Phdselective Oxidation Of Olefins Aro...mentioning
confidence: 99%
“…Rieske oxygenases catalyze oxygenations and oxidative heteroatom dealkylations of a broad number of contaminants including carboxylated, nitrated, halogenated, as well as N - and O -alkylated (poly)­aromatic structures. These substrate structures reflect the wide range of man-made chemicals such as pesticides, pharmaceuticals, industrial chemicals, and explosives. ,,, Despite the well-known role of Rieske oxygenases in biocatalysis, the factors that lead to successful substrate oxygenation are still largely elusive. Both structural elements of the oxygenase such as substrate tunnels and flexible loops as well as electronic interactions in the active site between the substrate and the non-heme Fe center appear critical for successful O 2 activation and substrate hydroxylation. ,,,, Yet, it remains unclear whether any of these structural and electronic factors are optimized in Rieske oxygenases as microorganisms adapt to alternative contaminants as primary substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Rieske oxygenases (ROs) are nonheme iron-containing enzymes that catalyze a remarkably expansive range of reactions and act upon a diverse group of substrate chemical types. Found widely across nature, the ROs are increasingly appreciated for their roles and applications in human health, , environmental biotechnology, agriculture, and chemoenzymatic synthesis. Collectively, the catalytic repertoire of the RO family exceeds even those of other well-studied oxygenases, including cytochrome P450, dinuclear iron-containing hydrocarbon monooxygenases, flavin oxygenases, and α-ketoacid-linked monooxygenases. , …”
Section: Introductionmentioning
confidence: 99%